PENERAPAN SISTEM JOB ORDER COSTING DALAM PENENTUAN HARGA JUAL PRODUK PADA CV. SATU SATU MEDIA UTAMA - Nangin, Anggelika S.; Nangoi, Grace B.; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
CV. Satu Satu Media Utama in calculating the cost of the product, has not calculated carefully, causing problems for the company that are unknown in detail and impact the selling price of the company's products. CV. Satu Satu Media Utama is a company engaged in Digital Printing Industry. This study aims to determine the role of Job Order Costing in determining the selling price of the product, using the method of calculating Full Costing and Variable Costing. Method of data analysis used in this research is descriptive qualitative. The results of research for the implementation of Job Order Costing system, the company has applied in the collection of product cost, but in the calculation of the cost of the company's products does not include marketing costs and depreciation costs of the machine into the calculation of overhead costs, and the company has not entered the price card of the order as the auxiliary card in the determination product selling price.Keywords: Job order costing, factory overhead cost, selling price